Impact of normalized COVID-19 prevention and control measures on lower respiratory tract infection pathogenesis in hospitalized children - Feng, Yuan; Zhang, Huaixiao; Zhang, Bo; Zhou, Yinfei; Yuan, Haibin (Frontiers in Public Health, 2024)
Objective This study aimed to investigate the epidemiological characteristics of common pathogens contributing to childhood lower respiratory tract infections (LRTIs) in Xiangtan City, Hunan Province before and during the coronavirus disease 2019 (COVID-19) pandemic. Methods A total of 11,891 enrolled patients, aged 1 month to 14 years, diagnosed with LRTIs and admitted to Xiangtan Central Hospital from January 2018 to December 2021 were retrospectively reviewed in this study. Specifically, the epidemiological characteristics of these pathogens before and during the COVID-19 pandemic were analyzed. Results There was a significant decrease in the number of children hospitalized with LRTIs during the COVID-19 pandemic (2020–2021) compared to data from 2018 to 2019 (before the COVID-19 pandemic). Of these cases, 60.01% (7,136/11,891) were male and 39.99% (4,755/11,891) were female. 78.9% (9,381/11,891) cases occurred in children under 4 years of age. The average pathogen detection rate among 11,891 hospitalized LRTIs children was 62.19% (7,395/11,891), with the average pathogen detection rate of 60.33% (4,635/7,682) and 65.57% (2,670/4,209) before and during COVID-19 pandemic, respectively. The detection rates of adenovirus (ADV), bordetella pertussis (BP) and moraxella catarrhalis (M. catarrhalis) decreased dramatically, while the detection rates of influenza viruses (IFV), parainfluenza viruses (PIV), respiratory syncytial virus (RSV), haemophilus influenzae (H. influenzae), streptococcus pneumoniae (S. pneumoniae), and staphylococcus aureus (S. aureus) increased significantly during the COVID-19 pandemic. Overall, RSV, mycoplasma pneumoniae (MP), H. influenzae, and IFV were the major pathogens causing LRTIs in hospitalized children before and during the COVID-19 pandemic. Conclusion Public health interventions for COVID-19 prevention are beneficial to reduce the incidence of LRTIs in children by limiting the prevalence of ADV, MP, BP, and M. catarrhalis, but which have limited restrictive effects on other common LRTIs-associated pathogens. Collectively, the data in this study comprehensively investigated the effects of COVID-19 pandemic on the epidemiological characteristics of respiratory pathogens, which will be beneficial for improving early preventive measures.